Career Orientation of Millennial Teenagers in Madura - Ishlakhatus Sa'idah; Moh. Ziyadul Haq Annajih; Diana Vidya Fakhriyani (State Islamic University (UIN) Salatiga, 2023)
This research aims to determine the description of career orientation among teenagers in Madura based on their identity. This research uses a qualitative design with a phenomenological approach. The primary data researchers use is obtained through in-depth interviews and observations in the form of the words and actions of people who are observed or interviewed based on research topics obtained from research subjects. Supporting data for this research was obtained from a literature study. The research subjects were seven people with the criteria: (1) millennial teenagers aged 16 to 21 years, both men and women; (2) subjects residing in Madura; (3) subjects having emotional closeness to the researcher; and (4) subjects being willing to participate in research. Data analysis in this research uses phenomenological analysis techniques according to the research type used: phenomenal reduction, editorial reduction, and transcendental reduction. The research results include: first, the criteria and type of career they dream of, prioritizing thinking abilities (not physical), being relaxed, and having special skill qualifications. Second, the underlying motives for millennial teenagers in Madura in determining their dream career are based, among other things, on a sense of comfort, money, or salary, not feeling pressured, and having the value of service. Third, the driving figures in career choice are family and friends. Fourth, career achievement standards can be measured by the ability to develop an independent, private business that is developed from their dream profession, and the target retirement age for Madurese millennial teenagers is around 40–50 years old.